2020
DOI: 10.1007/s10862-020-09799-3
|View full text |Cite
|
Sign up to set email alerts
|

The DSM-5 with Limited Prosocial Emotions Specifier for Conduct Disorder: a Systematic Literature Review

Abstract: DSM-5 added a categorically defined specifier ('with Limited Prosocial Emotions'; LPE) for the diagnosis of conduct disorder (CD). This paper systematically reviews the evidence base for this specifier in children and adolescents who are diagnosed with CD. Computer-assisted searches were executed and identified 181 potentially relevant papers. Eventually, nine papers were included in this review, referring to eight unique samples. All studies constructed an LPE measure by pulling the same items from the same r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
(64 reference statements)
2
22
0
Order By: Relevance
“…This finding, and its consistency with some research, 8,23 supports speculations that the LPE specifier has diagnostic value in the absence of CD or CP. 47 Yet, not all studies have revealed such differences, 6,48 underscoring the need for further study on features and outcomes of LPE Only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding, and its consistency with some research, 8,23 supports speculations that the LPE specifier has diagnostic value in the absence of CD or CP. 47 Yet, not all studies have revealed such differences, 6,48 underscoring the need for further study on features and outcomes of LPE Only.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, well-known scales that have been used in the development of and research on the LPE specifier, typically failed to provide support for the LPE subtyping scheme (Supplement 1, available online). 6 Thus, this scale might be informative for future work. Second, diagnostic interviews designed to assess the LPE specifier or to determine the presence of CD, were not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of CU traits as a conduct disorder specifier by the APA in 2013, more than 50 literature reviews about CU traits in children and adolescents have been published (e.g., Web of Science, 2013–2020). Although most of the reviews cover several aspects, they mainly study and discuss (a) diagnostic legitimacy, e.g., [ 6 , 24 , 66 ]; (b) assessment, including the validity of measurement instruments, e.g., [ 15 , 23 ]; (c) etiology, e.g., [ 33 , 35 ]; (d) developmental trajectories and outcomes, e.g., [ 28 , 51 ] and (e) intervention, e.g., [ 28 , 67 ]. Even flourishing literature review on CU traits (see above), to date and as far as we know, no review deals about links between CU traits and each dimension of human functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, researchers have become increasingly interested in psychopathy or psychopathic traits in juveniles. As a result, for example, limited pro social emotions (a term related to callous-unemotional traits, one of the features of psychopathy) have been included as a specifier of Conduct Disorder (CD) in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [ 2 ] in order to capture a high-risk subgroup of juveniles with CD [ 19 , 29 ].…”
Section: Introductionmentioning
confidence: 99%